PENERAPAN DENDA MURABAHAH MENURUT FATWA DEWAN SYARIAH NASIONAL DSN/MUI (STUDI DI PT. BANK MUAMALAT INDONESIA CABANG PADANGSIDIMPUAN) - Fadly Fadly (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2018)
Bank Moslem law as institute of intermediary monetary which is activity the core important mustering and channelling money by is assorted of product and its mechanism of course face various dynamics, like existence of the fact that some of client cannot fulfill its obligation according to time which have been specified resulting delay in deferred payment. In this case bank side strive in overcoming the problem of tersbut by applying penalty at defrayal which in accomodating according to Religious Advices Council Moslem law National of MUI the which client can be fined by if overdue client in conducting deferred payment.In Islam someone law obliged in honour of and obey each every entrusted trust or agreement to it. If someone have got defrayal or credit of bank, hence he have got trust of others ( deposan or owner of capital), if the debitor do default, hence can be told have done wanprestasi. One who do wanprestasi can be imposed by sanction or action as according to condition and reason him. In this case affect from client doing wanprestasi result natural bank of loss, because in doing addiction not rarely bank release expense, start from administrative affair, till the expense of big to rent lawyer.Council Moslem law National of MUI in its religious advices of Number 17/DSN-MUI/IX/2000 About Sanction of Client Can Procrastinating Payment enable bank of syari'ah fine to assumed client can but do not pay for obligation to bank of syari'ah. Hence from that writer wish to study furthermore as applying of penalty in Moslem law bank.